2014
DOI: 10.1093/fampra/cmu036
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the symptom abdominal pain--a systematic review and meta-analysis

Abstract: There is a high prevalence of patients consulting GPs for abdominal pain. The review identified a comparably high rate of acute underlying diseases in need of further investigation or therapy. At the same time, the underlying cause of the complaints often remains unexplained. Further symptom-evaluating studies are necessary, ideally using standardized methodology in order to gain sufficient evidence for developing much-needed guidelines and decision support tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 17 publications
3
72
1
8
Order By: Relevance
“…Alleviating pain has historically not been deemed appropriate in the early stages of presentation with acute abdomen, as it may conceal clinical signs of peritonitis. Although several published reports condemn this regimen [6,15], the present findings show that the care practice is not always in line with research findings. Analgesics in the ED often needed to be prescribed by a physician, while a wide variety of range orders in the ambulance care and at the surgical wards were common.…”
Section: Discussioncontrasting
confidence: 87%
“…Alleviating pain has historically not been deemed appropriate in the early stages of presentation with acute abdomen, as it may conceal clinical signs of peritonitis. Although several published reports condemn this regimen [6,15], the present findings show that the care practice is not always in line with research findings. Analgesics in the ED often needed to be prescribed by a physician, while a wide variety of range orders in the ambulance care and at the surgical wards were common.…”
Section: Discussioncontrasting
confidence: 87%
“…In the community setting, a recent literature review by Viniol et al concluded that there is much need for better guidelines and decision-support tools for such patients in the primary care. 7 Moreover, during the triage sequence in the emergency department, physicians are used to applying risk-stratification calculations in order to assess, both short- and long-term prognosis, according to their working diagnosis. For example, Dipaola et al discussed the importance of risk stratification of patients presenting with syncope to the ED, 8 Kang et al present a risk stratification model for cases of acute pyelonephritis in order to indicate cases necessitating hospital admission, 9 Spinar et al, 10 and others, further improved our knowledge regarding the appropriate risk stratification process of patients with acute heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal pain is a common problem & constitutes about 3% of the hospital visit among adults [1]. It may be acute or chronic.…”
Section: Introductionmentioning
confidence: 99%